Decolonizing the Environmental Issue: dismantling the “Contributions of Nature to People” - di Pasquo, Federico; Ocampo, Carolina; Matías, Lamberti; Busan, Tomas; Pallitto, Nahuel (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
The United Nations System (UN), along with a series of linked Intergovernmental Organizations (IOs), are presented as some of the most important actors on the world stage. This System directly influences public policies, laws, and instruments of the different States of Latin America and the Caribbean.(1) Under this premise, we study one of these organizations, aimed at the environmental problems of our region, called: "Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services" (IPBES). Specifically, we investigate this platform based on the document entitled: "Regional Assessment Report on Biodiversity and Ecosystem Services for the Americas".(2) We argue that IPBES (like the entire UN System) functions as an ideological apparatus that implements Western global designs that legitimize the inferiorization of non-Western knowledge and epistemologies.(3) Thus, our objective is to dismantle the epistemic strategy used by IPBES, called "Nature’s Contributions to People" (NCP), to evidence and denounce the privilege granted to eropean-north-american scientific-ecological knowledge. Our results aim to denounce the privileges granted to ecological knowledge through the theoretical strategy implemented by IPBES (NCP). This theoretical strategy organizes and stabilizes a representation of our natures through categories that support european-north-american dominance and that, tacitly, inferiorize knowledge from our region. As has been pointed out, the reverse of privileging scientific knowledge is the inferiorization of other knowledge